Unique laparoscopic emergency management of traumatic obstructed abdominal wall hernia: A case report and review of literature - Arwa M. Aljuhani; Ghaith A. Al Saied; Arjmand Reyaz; Mohammed A. Alkahlan; Ibrahim M. Aljohani; Muhammed M. Abukhater (International Journal of Abdominal Wall and Hernia Surgery)
Traumatic abdominal wall hernia (TAWH) is a rare clinical occurrence, with only limited cases published since 1906. This type of hernia is primarily caused by low- or high-energy blunt force trauma, resulting in damage to abdominal wall musculature while the skin is intact. The diagnosis and management of TAWH poses a lot of challenges and complexities. Herein, we present a case of a 32-year-old male Saudi patient who sustained significant abdominal trauma as a driver involved in a front collision while wearing a seat belt. Upon arrival at the trauma center, the patient was hemodynamically stable and exhibited clinical signs of left flank bulge, seat belt sign, and abdominal bruising. First, a focused assessment with sonography for trauma (FAST) was performed, which revealed minimal free fluid in the abdomen. Subsequent contrast-enhanced IV computed tomography (CT) scan confirmed a 3.6-cm left lateral abdominal wall defect with herniation of short segments of the large and small bowel loops and adjacent subcutaneous fluid. Following initial observation, the patient developed signs of bowel obstruction. A repeat CT scan showed interval progression of the hernia, partial small bowel obstruction, and other concerning findings. An emergency laparoscopic exploration revealed a large defect at the left lumber region containing omentum and long segments of the small bowel with mild distension. The bowel and omentum were reduced. The surgical repair included herniorrhaphy and mesh placement. The patient recovered well and was discharged on the third postoperative day. This case underscores the importance of thorough evaluation and timely intervention in TAWHs. Rapid surgical management, aided by advanced imaging techniques, can lead to favorable outcomes even in complex cases involving bowel herniation and associated complications.